2022
DOI: 10.1038/s41366-022-01175-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adipose inflammation by cellular retinoic acid-binding protein 1

Abstract: Objectives Obesity, a metabolic syndrome, is known to be related to inflammation, especially adipose tissue inflammation. Cellular interactions within the expanded white adipose tissue (WAT) in obesity contribute to inflammation and studies have suggested that inflammation is triggered by inflamed adipocytes that recruit M1 macrophages into WAT. What causes accumulation of unhealthy adipocytes is an important topic of investigation. This study aims to understand the action of Cellular Retinoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This view centers on the well-known genomic activities of RA, mediated by nuclear RA receptors (RARs) that regulate gene expression, generally referred to as the canonical activities of RA ( Wei, 2003 ; Cunningham and Duester, 2015 ). An increasing number of studies have identified rapid cytosolic (without involving nuclear RARs) activities of RA, which could modulate cytosolic signaling pathways as demonstrated in multiple cell types, including adipocytes ( Lin, 2020a ; Wei et al, 2022 ), cardiomyocytes ( Park et al, 2018 ; Park et al, 2019 ), stem cells ( Persaud et al, 2013 ; Lin et al, 2017 ), and neurons ( Lin, 2020b ; Lin et al, 2022 ). Recently, it has been established that CRABP1 acts as a direct mediator of these rapid cytosolic activities of RA in a cell context-dependent manner, referred to as non-canonical RA activities reviewed in Nagpal and Wei (2019) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This view centers on the well-known genomic activities of RA, mediated by nuclear RA receptors (RARs) that regulate gene expression, generally referred to as the canonical activities of RA ( Wei, 2003 ; Cunningham and Duester, 2015 ). An increasing number of studies have identified rapid cytosolic (without involving nuclear RARs) activities of RA, which could modulate cytosolic signaling pathways as demonstrated in multiple cell types, including adipocytes ( Lin, 2020a ; Wei et al, 2022 ), cardiomyocytes ( Park et al, 2018 ; Park et al, 2019 ), stem cells ( Persaud et al, 2013 ; Lin et al, 2017 ), and neurons ( Lin, 2020b ; Lin et al, 2022 ). Recently, it has been established that CRABP1 acts as a direct mediator of these rapid cytosolic activities of RA in a cell context-dependent manner, referred to as non-canonical RA activities reviewed in Nagpal and Wei (2019) .…”
Section: Introductionmentioning
confidence: 99%
“…In embryonic stem cells, adipocytes, and neural stem cells that are extremely sensitive to growth factor-elicited signaling pathways such as the mitogen-activated protein kinase (MAPK) pathway ( Zhang et al, 2002 ; Wei, 2013 ), CRABP1 is important for stem cell proliferation ( Persaud et al, 2013 ; Lin et al, 2017 ), exosome secretion ( Lin et al, 2021 ), and adipokine production ( Wei et al, 2022 ). The MAPK pathway is initiated by the membrane-bound Ras GTPase, which serves as a molecular switch to activate the Raf-MEK-ERK kinase cascade upon growth factor stimulation ( Cargnello and Roux, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recently uncovered CRABP1mediated cytosolic activities are referred to as non-canonical activities of RA, in contrast to widely known canonical activities of RA mediated by nuclear RA receptors (RARs) that typically act to regulate gene expression [3,4]. Using Crabp1 gene knockout (CKO) mice and cell models, we have demonstrated that CRABP1 plays roles in multiple cellular processes and disease conditions [5], such as neuron stem cell proliferation [6], motor neuron (MN) function [7], endocrine homeostasis [8,9], exosome secretion [10] and adipocyte hypertrophy [11,12]. Most of these processes involve the modulation of either the ERK or the CaMKII pathway by CRABP1.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that mitochondrial dysfunction underlines numerous diseases including cardiovascular diseases, metabolic disorders, and neurodegenerative diseases, such as ALS. Interestingly, in CKO embryonic stem cells (unpublished) and adipocytes [11], there is a significant reduction in mitochondrial DNA (mtDNA) content. Additionally, our unpublished preliminary studies have detected increased abnormality in mitochondrial function in CKO spinal cord tissues.…”
Section: Introductionmentioning
confidence: 99%